2017
DOI: 10.3126/kumj.v13i3.16811
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Serum Intact Parathyroid Hormone Level and Hematocrit in Chronic Kidney Disease Patients

Abstract: Background Anemia is a common complication of chronic kidney disease. There are various causes of anemia in chronic kidney disease patients on hemodialysis. Secondary hyperparathyroidism is one of the less recognized causes of anemia in chronic kidney disease patients.Objectives The main objective of the study is to find the correlation between intact parathyroid hormone and hematocrit level in chronic kidney disease (CKD) patients undergoing hemodialysis.Method Verbal consent was taken from all the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…In this context, Goel et al (27) reported that the level of intact PTH in 174 CKD patients on hemodialysis was 440.9 ± 397.8 pg/ml. Adhikary et al (28) also reported that intact PTH level in 80 CKD participants having an indication of hemodialysis was 458.12 ± 101.27 pg/ml. In addition, Gallieni et al (16) found a significant elevation (p<0.001) in serum PTH levels in stage 5 CKD patients at the end of their study when compared with baseline values.…”
Section: Discussionmentioning
confidence: 94%
“…In this context, Goel et al (27) reported that the level of intact PTH in 174 CKD patients on hemodialysis was 440.9 ± 397.8 pg/ml. Adhikary et al (28) also reported that intact PTH level in 80 CKD participants having an indication of hemodialysis was 458.12 ± 101.27 pg/ml. In addition, Gallieni et al (16) found a significant elevation (p<0.001) in serum PTH levels in stage 5 CKD patients at the end of their study when compared with baseline values.…”
Section: Discussionmentioning
confidence: 94%
“…8 In the study of Adhikary et al, which included chronic renal patients aged between (29:70) years, it indicated an inverse relationship between normal hematocrit and parathyroid levels, which is the same results revealed by our current research. 9 More recently, Azeem et al evaluated 110 Patients undergoing maintenance hemodialysis with PTH levels greater than 300 ng/L. The authors concluded that patients with hyperparathyroidism frequently develops anemia.…”
Section: Discussionmentioning
confidence: 99%
“…A anemia é um achado comum nos pacientes renais crônicos, surgindo precocemente no curso da DRC 17 . Assim como neste estudo, encontrou-se uma relação inversa entre os valores de hematócrito e de PTH, sugerindo esta situação como uma possível explicação para os casos de anemia mesmo em tratamento com eritropoietina recombinante (EPO) 18 .…”
Section: Discussionunclassified